Book Review of “Therapist and Client: A Relational Approach to Psychotherapy” - Iwakabe, Shigeru (Canadian Journal of Counselling and Psychotherapy, 2015)
Patrick Nolan’s book Therapist and Client: A Relational Approach to Psychotherapy is a practical guide to an integrative relational approach, which synthesizes a range of approaches from relational psychoanalysis to humanistic therapies and body-oriented work. The author thoroughly reviews findings from attachment, developmental, and neuroscience research to provide a firm empirical basis for his approach. The book is filled with numerous detailed case examples illustrating the intersubjective aspects of therapy. This valuable guide offers a wealth of innovative ideas for psychotherapists of all levels to deepen their understanding of the healing power of the therapeutic relationship.